Bioprocess development for chlorophyll extraction from microalgae - Halim, R.; Danquah, Michael (2012)
© 2013 Springer Science+Business Media New York. All rights reserved. Chlorophyll, a green pigment found abundantly in plants, algae, and cyanobacteria, plays a critical role in sustaining life on earth and has found many applications in pharmaceutical, food, as well as cosmetic industries. Because of their high intracellular chlorophyll accumulations (up to 10% of cell dry weight), green microalgae are recognized as promising alternative chlorophyll sources. Successful co-production of a high value product such as chlorophyll in a microalgal bio-refinery is desirable as it will alleviate the overall cost of producing microalgal biodiesel. This chapter evaluates the bioprocess engineering required to recover and to purify chlorophyll molecules from microalgae. The use of organic solvents and supercritical fluids to extract microalgal chlorophyll on a commercial scale is examined. The use of chromatographic techniques to purify the recovered chlorophylls is also reviewed. Finally, the chapter ends by presenting a case study which investigates the use of organic solvents (acetone and methanol) to extract chlorophyll from Tetraselmis suecica on a laboratory scale.